2021
DOI: 10.1038/s41408-021-00591-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic assessment of measurable residual disease in favorable-risk acute myeloid leukemia in first remission, treatment, and outcomes

Abstract: We aimed to investigate outcomes of different post-remission treatment (PRT) choices based on dynamic measurable residual disease (MRD) by multiparameter flow cytometry in favorable-risk AML (FR-AML). Four hundred and three younger patients with FR-AML in first complete remission (CR1) were enrolled in this registry-based cohort study, including 173 who received chemotherapy (CMT), 92 autologous stem cell transplantation (auto-SCT), and 138 allogeneic SCT (allo-SCT). The primary endpoint was the 5-year overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…reported that <3 log reduction of RUNX1/RUNX1T1 transcripts in comparison to the pretreatment baseline values after three courses of chemotherapy indicated a higher relapse risk 6,9 . We recently reported that the favorable‐risk MRD‐positive patients after three chemotherapy cycles or recurrent MRD showed higher CIR and benefited from allo‐SCT 19 . In this study, MRD high after three courses of treatment was identified as an independent risk factor for relapse.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…reported that <3 log reduction of RUNX1/RUNX1T1 transcripts in comparison to the pretreatment baseline values after three courses of chemotherapy indicated a higher relapse risk 6,9 . We recently reported that the favorable‐risk MRD‐positive patients after three chemotherapy cycles or recurrent MRD showed higher CIR and benefited from allo‐SCT 19 . In this study, MRD high after three courses of treatment was identified as an independent risk factor for relapse.…”
Section: Discussionmentioning
confidence: 50%
“…Among patients who could not comply with the treatment recommendations described above due to patient bias or donor availability, MRD low patients underwent allo‐HSCT and MRD high patients underwent chemotherapy as postremission treatment. The cytarabine‐based consolidation therapy included the “3 + 3” regimen and an intermediate/high‐dose of cytarabine (2–3 g/m 2 ) twice each day on Days 1–3 19 . Allo‐SCT was also advised for patients who had relapsed after CMT 17 .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the notion of disease risk-adapted, measurable residual disease (MRD)-driven post-remission therapy has been developed. [1][2][3][4][5][6] Combining cytogenetic and molecular characterization with MRD has shown to improve prognosis stratification and treatment option selection. 1,3,4 Auto-HSCT, which is associated with a favorable safety profile, provides an alternative post-remission option for favorable-or intermediate-risk AML patients who have achieved an adequate MRD response or for whom allogeneic HSCT is not available.…”
Section: Introductionmentioning
confidence: 99%
“…Auto‐HSCT, which is associated with a favorable safety profile, provides an alternative post‐remission option for favorable‐ or intermediate‐risk AML patients who have achieved an adequate MRD response or for whom allogeneic HSCT is not available 7,8 . In favorable‐risk AML, overall survival (OS) was similar among patients receiving chemotherapy, allo‐HSCT, or auto‐HSCT in the subgroups of achieving MRD negative after 1, 2, and 3 courses of chemotherapy, respectively 6 . Furthermore, auto‐HSCT demonstrated satisfactory outcomes with a 5‐year leukemia‐free survival of 97.3% in intermediate‐risk AML who achieved first complete remission (CR1) after one induction chemotherapy and maintained persistently negative MRD 5 .…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 , 10 , 11 , 12 In addition, the speed required to achieve remission and to clear the leukemic blasts may be important for the outcome and overall survival (OS) in patients with AML. 13 , 14 , 15 The number of induction courses needed to achieve remission may be an additional surrogate marker both for leukemic risk as well as the quality of the remission in AML predicting response and transplantation outcome. 16 In a previously reported study addressing patients undergoing allogeneic stem cell transplantation (HSCT), Lim SJ et al analyzed the post‐transplantation outcome in 45 patients with high‐risk AML that achieved complete remission (CR) after 1–2 induction versus 3 or more induction courses pre‐HSCT from a matched sibling or unrelated donors and demonstrated a trend for better progression‐free survival and OS in the formers.…”
Section: Introductionmentioning
confidence: 99%